Impacts on Tax Rate of Cigarette toward Economic Welfare of Thailand: Simultaneous Equation Analysis - NONTHAPOT, Sakkarin; WATCHALAANUN, Tanawat (Journal of Advanced Research in Law and Economics; Vol 9 No 6 (2018): JARLE Volume IX Issue 6(36) Fall 2018DO - 10.14505//jarle.v9.6(36).23, 2019)
This study aims to (1) know the influence factor on demand and supply cigarette  market of Thailand (2) estimate the economic welfare that affecting from the cigarette  excise tax rate and (3) evaluate the worthiness of cigarette tax policy which compare with  the cost related to the treatment of smoking patients. This research used the time series   data from 1984 to 2016 included 33 years. The influence factors on demand and supply are analyzed by using simultaneous equation, estimated by three stage least square (3SLS) method and economic welfare computation. Then, it calculates economic welfare and the cost related to the treatment of smoking patients. The results are found that that cigarette price has a negative relation on cigarette demand while the consumer price index has positive relation on demand. On the other hand, the prices have a positive relation on cigarette supply while the selling cost and exchange rate have a negative relation on supply. Moreover, cigarette tax and Gross Domestic Product have a positive relation on the cigarette price. The simulation forecasting results are shown that the rising of cigarette tax rate increases the tax revenue; however it decreases economic welfare that has an effect on producer’s surplus more than consumer’s surplus. From the results, the tax policy is still worth on the economic welfare.